Day 1 Mon, October 09, 2017 2017
DOI: 10.2118/187384-ms
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Thomson Equation for Accurate Modeling of Pore Scale Thermodynamics of Hydrocarbon Solvents

Abstract: As stated by the classical Thomson equation, the pore scale thermodynamics of solvent is different from bulk conditions being critically controlled by capillary characteristics. This equation shows that the boiling points decrease remarkably as the pore size and interfacial tension become smaller. This paper investigates this phenomenon for hydrocarbon solvents experimentally and compares the results with the values obtained from the Thomson equation to test its applicability in modelling heavy-oil recovery by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Phase alteration is a commonly encountered phenomenon in many engineering applications and natural processes in underground reservoir systems or synthetic porous media. These include CO 2 sequestration, conventional and unconventional oil and gas production, geothermal systems, waste deposition, and synthetic porous systems such as filters. Throughout the primary production period of oil or gas, the decline of reservoir pressure leads to the vaporization of hydrocarbons, starting from the lighter components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase alteration is a commonly encountered phenomenon in many engineering applications and natural processes in underground reservoir systems or synthetic porous media. These include CO 2 sequestration, conventional and unconventional oil and gas production, geothermal systems, waste deposition, and synthetic porous systems such as filters. Throughout the primary production period of oil or gas, the decline of reservoir pressure leads to the vaporization of hydrocarbons, starting from the lighter components.…”
Section: Introductionmentioning
confidence: 99%
“…Small (nano)­capillaries have a major impact on the process as boiling occurs quicker (at lower temperatures) compared to larger capillaries. , Therefore, capillary size and distribution controls the whole process, meaning further phase change and the displacement and entrapment of the gas and liquid phases. In our prior studies, vaporization temperatures of various hydrocarbons were studied using different lab-scale capillary models such as Hele–Shaw silica-glass cells, microfluidics chips, and reservoir rocks (Berea sandstone, Indiana limestone, tight sandstone, and shale). These studies qualitatively and quantitively investigated the phase behavior (boiling temperatures and pressures of hydrocarbon solvents) and showed that phase change occurs more quickly as the medium becomes tighter.…”
Section: Introductionmentioning
confidence: 99%